2016
DOI: 10.1039/c6ra18112k
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid bicelles as a pH-sensitive nanocarrier for hydrophobic drug delivery

Abstract: Stabilized disc-like hybrid bicelles provide pH-sensitive release, preferable cellular uptake, tumor accumulation and therapeutic effect in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 69 publications
0
32
0
Order By: Relevance
“…Thanks to its hydrophobicity and cationic charge, DOX was readily loaded into DPPC/SC‐C 5 bicelles (Figure S15), and Dai et al. recently reported that bicelles successfully served as carriers for DOX . The resulting DPPC/SC‐C 5 /DOX bicelles, at a concentration of 0.1 wt % (net concentration of DOX=24 μ m ), were mixed with HepB3B cells in EMEM containing 10 % FBS, and incubated either in the bicelle state (25 °C) or in the micelle state (37 °C).…”
Section: Figurementioning
confidence: 99%
“…Thanks to its hydrophobicity and cationic charge, DOX was readily loaded into DPPC/SC‐C 5 bicelles (Figure S15), and Dai et al. recently reported that bicelles successfully served as carriers for DOX . The resulting DPPC/SC‐C 5 /DOX bicelles, at a concentration of 0.1 wt % (net concentration of DOX=24 μ m ), were mixed with HepB3B cells in EMEM containing 10 % FBS, and incubated either in the bicelle state (25 °C) or in the micelle state (37 °C).…”
Section: Figurementioning
confidence: 99%
“…Lin et al reported the formation of hydrophobic doxorubicin loaded hybrid bicelles generated from CFL and short phospholipids DHPC at the ratio of 7:2 via traditional thin film hydration method ( Figure 16). [52] It was found that the disc-like bicelles displayed similar significantly high stability to cerasome vesicles, but they had higher cellular uptake than spherical cerasomes. More importantly, drug-loaded bicelles exhibited pH-sensitive release behavior and could effectively inhibit the tumor growth.…”
Section: Novel Cerasomesmentioning
confidence: 99%
“…[50,51] Such hybrid bicelles have received widespread attention owing to the presence of the polyorganosiloxane surface, which offers remarkably higher stability than conventional phospholipid bicelles. [50,52] Moreover, such disc-like nanoparticles exhibit preferential cellular uptake and higher microvascular adhesion than spherical nanoparticles. [53][54][55][56][57] In addition, hybrid bicelles are capable of encapusulating hydrophobic drugs.…”
Section: Novel Cerasomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The planar bilayer region enriched in the long-chain lipids provides a favorable environment to study membrane proteins using various techniques, such as nuclear magnetic resonance (NMR), [4][5][6][7][8][9][10][11] X-ray crystallography, [12][13][14][15][16] and spectroscopy techniques. [17][18][19][20][21] Bicelles can also be used as delivery vehicles for membrane proteins or drugs, 22,23 or as templates for the synthesis of platinum nanowheels.…”
Section: Introductionmentioning
confidence: 99%